GlycoIP: an integrated platform for simultaneous and site-specific N/O-glycosylation analysis of human semen - Gaoshu Yan; Fei Cai; Keliang Wu; Qingyuan Cheng; Yong Zhang; Lin Fan (Frontiers in Chemistry)
Protein glycosylation plays a pivotal role in human semen, influencing various processes, such as spermatogenesis, maturation, sperm motility, capacitation, and fertilization. Despite its importance, the specific details regarding N/O-glycosylation within human semen proteins have largely remained unknown. To address this challenge, an integrated glycoproteomic platform (termed GlycoIP) was developed, enabling the simultaneous analysis of both intact N- and O-glycopeptides directly from human semen samples. Characterizing these intact glycopeptides is particularly challenging, yet it provides invaluable insights into the structure and function of both glycans and their attachment sites. In this study, our platform enabled the identification of 1,833 unique N-glycopeptides and 720 unique O-glycopeptides. This approach revealed extensive and precise site-specific N/O-glycosylation data, highlighting 438 potential O-glycosylation sites from 148 distinct O-glycoproteins. Notably, we conducted site-specific N/O-glycosylation profiling on several unique glycoproteins, including sperm equatorial segment protein 1 (SPESP1), which is located on human sperm, and plasma serine protease inhibitor (SERPINA5), which is presented in both sperm and seminal plasma. In summary, this platform provides a promising approach for comprehensive profiling of protein site-specific N/O-glycosylation within a single experiment. This advancement paves the way for further functional studies on glycoproteins and their roles in male infertility, enhancing our understanding of this complex field.